Identification of Leg Chemosensory Genes and Sensilla in the Apolygus lucorum - Li, Zibo; Zhang, Yaoyao; An, Xingkui; Wang, Qi; Khashaveh, Adel; Gu, Shaohua; Liu, Shun; Zhang, Yongjun (Frontiers in Physiology, 2020)
Apolygus lucorum (Hemiptera: Miridae), one of the main insect pests, causes severe damage in cotton and many other economic crops. As is well-known, legs play important roles in the chemoreception of insects. In this study, the putative chemosensory proteins in legs of A. lucorum involved in close or contact chemical communication of adult bugs were investigated using RNA transcriptome sequencing and qPCR methods. Transcriptome data of forelegs, middle legs and hind legs of adult bugs demonstrated that 20 odorant binding protein (OBP) genes, eight chemosensory protein (CSP) genes, one odorant receptor (OR) gene, one ionotropic receptor (IR) gene and one sensory neuron membrane protein (SNMP) gene were identified in legs of A. lucorum. Compared to the previous antennae transcriptome data, five CSPs, IR21a and SNMP2a were newly identified in legs. Results of qPCR analysis indicated that all these putative chemosensory genes were ubiquitously expressed in forelegs, middle legs and hind legs of bugs. Furthermore, four types of sensilla on legs of A. lucorum including sensilla trichodea (subtypes: long straight sensilla trichodea, Str1; long curved sensilla trichodea, Str2), sensilla chaetica (subtypes: sensilla chaetica 1, Sch1; sensilla chaetica 2, Sch2; and sensilla chaetica 3, Sch3), sensilla basiconca (subtypes: medium-long sensilla basiconca, Sba1; short sensilla basiconca, Sba2) and Böhm bristles (BB) were found using scanning electron microscopy. Additionally, the largest number of sensilla was observed on hind legs, while the forelegs had the smallest number of sensilla. Our data provide valuable insights into understanding the chemoreception of legs in A. lucorum.